Electronic Voting system for efficient Students' Elections in Kabarak University, Kenya. - Charles Ochieng' Oguk,; Moses Mwangi Thiga, (IJRDO - Journal of Social Science and Humanities Research, 2019)
Student elections in universities have over the years been conducted manually,  hence causing them to become very expensive, logistically complex, tedious and involving exercises; and often with low accuracy levels. This study examines the challenges of conducting student elections manually and presents an electronic alternative that demonstrates great advantages of reduced time and efficiency. The electronic voting system developed and tested at Kabarak University is a result of a consultative engagement with the student fraternity and utilizes a very basic but efficient approach to guarantee the sanctity of the process and accuracy in the tallying of the results. The system and development process served to demonstrate the applicability of electronic voting not only in the higher education context, but also in other contexts that require an infusion of efficiency in the voting processes.